Efforts To Improve Social Sciences Learning Outcomes Indonesian Cultural Diversity Material Through The Numbered Heads Together (NHT) Collaborative Learning Model for Fourth-Grade Students of SDN Baran - Prihma Sinta Utami; Friska Nur Kusumadewi; Tutik Saptiningsih (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2024)
The learning achievement in Social Studies, particularly among Grade 4 students at SD N Baran, is still low. The purpose of this study is to describe the improvement in Social Studies learning outcomes through the cooperative learning model of the NHT (Numbered Heads Together) type among Grade 4 students at SD N Baran. This research is a Classroom Action Research. The subject of the research was 9 students in Grade 4 at SD N Baran. The research used a qualitative approach. Data collection methods included both test and non-test techniques, such as observation. The data analysis methods used were quantitative and qualitative. The study was conducted in two cycles. The results showed that the average test score increased in each cycle. In the pre-action stage, the average score was 51.79, which increased by 12.30 points to 64 in Cycle I, and further rose to 81 in Cycle II with an improvement of 17 points. In the pre-action stage, 0% of students achieved mastery; this increased by 11% to 22% in Cycle I. In Cycle II, mastery increased by 67%, so that student mastery in Cycle II reached 89%. This indicates that Social Studies learning outcomes improved from Cycle I to the end of Cycle II. It can be concluded that the application of the cooperative learning model of the NHT type can improve student learning outcomes.